(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The modern food industry shows a growing demand for functional extruded products enriched with natural ingredients. However, the interactions within multi-component systems, such as grain-vegetable blends, during extrusion are complex and not fully understood. The purpose of this study was to conduct a comparative analysis of the effects of extrusion processing and the addition of carrot and beet on the rheological properties (kinematic viscosity) of pastes derived from wheat, corn, and barley, in order to identify these synergistic effects. Methods. Three types of grain (wheat, corn, barley) and their blends with fresh carrot or beet puree (5% w/w) were processed using a single-screw extruder under constant thermomechanical conditions. To evaluate the changes in starch properties, aqueous suspensions of the ground extrudates were prepared. The kinematic viscosity of the resulting filtrates was measured at a controlled temperature using a capillary viscometer and compared with the viscosity of pastes from native grains. Results. Extrusion processing significantly increased the kinematic viscosity of aqueous filtrates for all grain samples compared to their native counterparts, with the most pronounced effect observed for barley. The addition of vegetable components had a varied, grain-dependent effect. Carrot addition consistently caused a slight increase in viscosity for all cereals, which is attributed to the thickening effect of soluble pectins. In contrast, beet addition showed a complex behavior: it had a negligible effect on wheat paste viscosity, slightly increased it for corn, but caused a dramatic decrease for the barley-based extrudate. Conclusion. The study demonstrates that the impact of vegetable additives on the rheological properties of extruded products is highly dependent on the specific grain matrix. The results reveal a strong synergistic effect between the sucrose-rich beet and the unique polysaccharide system of barley. It is concluded that sucrose acted as an effective plasticizer, intensifying the thermomechanical degradation of barley polymers during extrusion, which led to a significant reduction in paste viscosity. These findings highlight the importance of selecting specific grain and vegetable combinations to control the final product’s rheological properties and texture.